From the eyes of Bragança – a poetics of the window (Palíndromo, 2023)
The text reports the course of research based on the arts, part of a case study carried out in the city of Bragança, in Portugal. The proposal aims to capture and (re)interpret graphically, from drawings in loco, windows perceived in the streets of the historic area, which aroused visual interest and affection in the process of observation and fruition in daily walks. In the fall of 2021, more than 40 sketchs of the most varied window styles were carried out, with an emphasis on antithetical issues such as the back and forth space, inside and outside, preservation and neglect, public and private, belonging and abandonment. The window, which symbolically represents the eye of dwellings, transits between the concrete and the imaginary, between the popular and the particular, far beyond its constructive function.
Keywords: drawing; window; sketches; visual arts; Bragança